Trends in the prevalence of hepatitis B infection among women giving birth in New South Wales. Issue 7 (17th April 2017) - Deng, Lucy; Reekie, Joanne; Ward, James S; Hayen, Andrew; Kaldor, John M; Kong, Marlene; Hunt, Jennifer M; Liu, Bette
Abstract: Objectives: To evaluate the effect of targeted and catch‐up hepatitis B virus (HBV) vaccination programs in New South Wales on HBV prevalence among women giving birth for the first time. Design: Observational study linking data from the NSW Perinatal Data Collection for women giving birth during 2000–2012 with HBV notifications in the NSW Notifiable Conditions Information Management System. Main outcome measures: HBV prevalence in Indigenous Australian, non‐Indigenous Australian‐born, and overseas‐born women giving birth. Results: Of 482 944 women who gave birth to their first child, 3383 (0.70%) were linked to an HBV notification. HBV prevalence was 1.95% (95% CI, 1.88–2.02%) among overseas‐born women, 0.79% (95% CI, 0.63–0.95%) among Indigenous Australian women, and 0.11% (95% CI, 0.09–0.12%) among non‐Indigenous Australian‐born women. In Indigenous Australian women, prevalence was significantly lower for those who had been eligible for inclusion in the targeted at‐risk newborn or universal school‐based vaccination programs (maternal year of birth, 1992–1999: 0.15%) than for those who were not (born ≤ 1981: 1.31%; for trend, P < 0.001). There was no statistically significant downward trend among non‐Indigenous Australian‐born or overseas‐born women. HBV prevalence was higher among Indigenous women residing in regional and remote areas than those in major cities (adjusted odds ratio [aOR], 2.23; 95% CI, 1.40–3.57), but lower for non‐Indigenous (aOR, 0.39; 95% CI, 0.28–0.55) and overseas‐born women (aOR, 0.61; 95% CI, 0.49–0.77). Conclusion: Among women giving birth, there was a significant reduction in HBV prevalence in Indigenous women associated with the introduction of the HBV vaccination program in NSW, although prevalence remains higher than among non‐Indigenous Australian‐born women, and it also varies by region of residence. Continuing evaluation is needed to ensure that the prevalence of HBV infections continues to fall in Australia.